Monitoring of microvascular calcification by time-resolved photoacoustic microscopy - Haigang Ma; Yinshi Yu; Yahui Zhu; Hongjun Wu; Haixia Qiu; Ying Gu; Qian Chen; Chao Zuo (Photoacoustics)
Monitoring of microvascular calcification (MC) is essential for the understanding of pathophysiological processes and the characterization of certain physiological states such as drug abuse, metabolic abnormality, and chronic nephrosis. In this work, we develop a novel and effective time-resolved photoacoustic microscopy (TR-PAM) technology, which can observe the obvious microvascular bio-elastic change in the development process of the MC owing to the calcium deposition along vascular walls.The feasibility of the TR-PAM imaging was validated using a group of agar phantoms and ex vivo tissues. Furthermore, MC pathological animal models were constructed and imaged in situ and in vivo by the TR-PAM to demonstrate its capability for the bio-mechanical monitoring and characterization of MC, and experimental results were consistent with the pathological knowledge. The feasibility study of monitoring MC by the TR-PAM proves that this technique has potential to be developed as a superficial microvascular bio-mechanical assessment method to supplement current clinical strategy for prediction and monitoring of some diseases.